Changes in the Mental Health Indicators and Training Opportunities for Estonian Elite Athletes Compared to the COVID-19 Isolation Period - Anna-Liisa Tamm; Ülle Parm; Anu Aluoja; Tuuli Tomingas (MDPI AG, 2022)
Background: In spring 2020, two-thirds of Estonian elite athletes had symptoms of emotional distress. The aim of this study was to evaluate the mental health indicators and training opportunities for elite Estonian athletes a year after the complete COVID-19 isolation period compared to June 2020. Methods: In both cross-sectional studies, athletes completed self-reported questionnaires, including the Emotional State Questionnaire. Descriptive statistics, t-tests, and Chi2 tests were applied to compare the study groups (p < 0.05). Results: A total of 172 out of approximately 600 elite Estonian athletes participated in the survey (102 in 2020 and 70 in 2021). More than a year after the COVID-19 lockdown period, the mental health problems of elite athletes (particularly the symptoms of depression and fatigue) are even greater concern than in June 2020, despite the recovery in training conditions and competition. Of all of the subjects, 80% had high levels of distress in 2021 compared to 36% in 2020. According to the athletes, the availability of health care services was good (78.6%), but there was a lack of close cooperation with the coach. However, the athletes considered their coaches to be their main supporters, along with their family members and partners. Only 4.3% of the respondents considered a sports psychologist to be their main supporter (n = 6). Conclusions: More than a year after the COVID-19 lockdown period, the mental health indicators of Estonian elite athletes were worrisome. Most of subjects had high levels of distress even though their training conditions had returned to normal (i.e., to as they had been before COVID-19).